Recent microencapsulation trends for enhancing the stability and functionality of anthocyanins: a review - Ijod, Giroon; Mohamed Nawawi, Nur Izzati; Anwar, Farooq; Abd Rahim, Muhamad Hafiz; Ismail-Fitry, Mohammad Rashedi; Mohd Adzahan, Noranizan; Mohamad Azman, Ezzat (The Korean Society of Food Science and Technology, 2024)
Anthocyanins (ACNs) are water-soluble pigments in various fruits and vegetables known for their high antioxidant activity. They are used as natural food colorants and preservatives and have several medicinal benefits. However, their application in functional foods and nutraceuticals is often compromised by their low stability to heat, oxygen, enzymes, light, pH changes, and solubility issues. Spray drying has emerged as an effective microencapsulation technique to enhance the shelf life, quality, and stability of ACNs. This manuscript reviews the latest scientific developments in spray drying microencapsulation of ACNs-rich fruit extracts. Process optimization and the stability and physicochemical properties of the spray-dried, microencapsulated ACNs-rich powders are discussed. This review also covers functional food and nutraceutical applications and introduces novel encapsulation methods, such as freeze-drying, supercritical carbon dioxide (SC-CO2), coacervation, drum drying, and electrospraying, highlighting their potential in improving the utility of ACNs-rich fruit extracts.